2016
DOI: 10.1002/j.2334-5837.2016.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Painting Systems: From Art to Systems Architecting

Abstract: Systems engineering has successfully contributed to develop complex systems in industries such as defense, space, energy, or transportation. Systems in those industries have in common their engineered or socio‐technical natures. However, systems engineering has been understood for a long time as both an art and a science. As a matter of fact, principles and practices of systems engineering have been exhibited in the creation of film original score, a major artistic endeavor. Therefore, it is sensible to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Systems architects also resort to rules, called in this case heuristics, that guide the structural form and the dynamic behaviour of an architecture to reduce its complexity (Maier & Rechtin, 2009). A study compared the sets of rules in the arts and in systems architecture and identified two sets of strategies that were employed by master artists and systems architects to achieve elegance (Salado, Iandoli, & Zollo, 2016):…”
Section: Elegant Systems and Core Concepts From Artmentioning
confidence: 99%
“…Systems architects also resort to rules, called in this case heuristics, that guide the structural form and the dynamic behaviour of an architecture to reduce its complexity (Maier & Rechtin, 2009). A study compared the sets of rules in the arts and in systems architecture and identified two sets of strategies that were employed by master artists and systems architects to achieve elegance (Salado, Iandoli, & Zollo, 2016):…”
Section: Elegant Systems and Core Concepts From Artmentioning
confidence: 99%
“…The first discussed how principles and practices of systems engineering are exhibited in the composition of a film original score, which focused on reducing complexity (Salado and Salado, 2015). The second discussed methods used by master painters to reduce effective complexity (Salado, Iandoli, and Zollo, 2016). Effective complexity refers to the subjective interpretation of a model by the observer -a fundamental skillset of both master artists and master system architects (Gell-Mann, 1994).…”
Section: Improving System Architecture Competenciesmentioning
confidence: 99%
“…Other heuristics provide guidance for the dynamic nature of systems: "it's the perceptions, not the facts, that count," of "if the politics don't fly, the hardware never will" (Maier and Rechtin, 1997). The first set relate to what we call noise killing strategies (Salado, Iandoli, and Zollo, 2016), which address the simplification of a complex concept or system to its essential core constructs. The second set address meaning adding strategies (Salado, Iandoli, and Zollo, 2016), those that represent the complexity of the system by highlighting the interaction of those constructs.…”
Section: Improving System Architecture Competenciesmentioning
confidence: 99%
See 2 more Smart Citations